PENERAPAN STRATEGI EVERYONE IS TEACHER HERE DALAM MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PADA MATA PELAJARAN SOSIOLOGI KELAS X-A DI MAN 1 KOTA PROBOLINGGO - Babul Bahrudin (UNZAH Genggong, 2022)
Learning strategies are a way for teachers to make the class more active. The use of learning strategies will make it easier for teachers to manage the class and increase motivation and learning achievement. One of the learning strategies that can be chosen by teachers is the Everyone Is a Teacher Here strategy which requires students to be more active, encourage learning motivation and improve student achievement. This study aims to 1) examine the implementation of the Everyone Is a Teacher Here strategy in increasing motivation and learning achievement in Sociology subjects in class X-A at MAN 1 Probolinggo City. 2) examine whether the implementation of the Everyone Is a Teacher Here strategy can increase motivation and learning achievement in the Sociology subject class X-A at MAN 1 Probolinggo City. This research is classroom action research (CAR) using a descriptive qualitative approach. Methods of data collection using the method of observation, interviews and documentation. From the two cycles that were applied, it can be seen in the evaluation of the post test scores, the average student got a good score. In the first cycle, the pre-test was 63%, in the second cycle, the post-test was carried out with an average value of 79.61%. This means that the students are enthusiastic in learning and the Everyone Is a teacher Here strategy has succeeded. Keyword: Learning Strategy, Motivation, Learning Achievement, Everyone Is a Teacher Here